Achieving successful evidence-based practice implementation in juvenile justice: The importance of diagnostic and evaluative capacity. (October 2015) - Walker, Sarah Cusworth; Bumbarger, Brian K.; Phillippi, Stephen W.
Highlights: We conduct a policy analysis of three states with successful evidence-based practice implementation for juvenile justice and violence prevention. We examine how data driven systems to support diagnostic and evaluative capacity in these sites were critical to program successes. The use of data driven decision making at each stage of implementation in these three states increased stakeholder buy in, facilitated program selection, funding decisions and program-site matches. Building infrastructure for diagnostic and evaluative capacity will enhance jurisdictions' ability to respond flexibly and with rigor to changing political and funding climates. Abstract: Evidence-based programs (EBPs) are an increasingly visible aspect of the treatment landscape in juvenile justice. Research demonstrates that such programs yield positive returns on investment and are replacing more expensive, less effective options. However, programs are unlikely to produce expected benefits when they are not well-matched to community needs, not sustained and do not reach sufficient reach and scale. We argue that achieving these benchmarks for successful implementation will require states and county governments to invest in data-driven decision infrastructure in order to respond in a rigorous and flexible way to shifting political and funding climates. We conceptualize this infrastructure as diagnostic capacity and evaluative capacity: Diagnostic capacity is defined as the process of selecting appropriate programing and evaluative capacity is defined as the ability to monitor and evaluate progress. Policy analyses of Washington State, Pennsylvania and Louisiana's program implementation successes are used to illustrate the benefits of diagnostic and evaluate capacity as a critical element of EBP implementation.